The Design Lodge : Reflections on the “studio” and a lexical shift towards life-centred architectural education - Fortin, David (Enquiry The ARCC Journal for Architectural Research, 2022)
This essay posits the role that the spaces for architectural production have played in supporting a design ethos that has historically neglected our relationship with the Land, and how its reconceptualization could contribute to a ‘spiritual and cultural’ shift through a placed-based ethical framework. More specifically, the space where design typically takes place is most often described in English as the “studio”, a term that has been adopted by universities and professional offices alike, and is broadly considered the core of architectural education and production around the world. Yet, surprisingly, we rarely question - why a “studio”? What is the nature of a “studio” exactly, and how does this potentially impact how we teach design and, subsequently, what we design? Can an element of the sacred infiltrate the spaces of architectural production in the twenty-first century in an effort to prioritize the flourishing of all life on our planet, and how can Indigenous knowledge guide us along this path? The essay first examines the history of the “studio” and questions its ongoing relevance, as well as recent alternatives. This is followed by a proposition for the concept of a “design lodge” that might best be able to inspire “transformational” change in architectural education by transcending conventional fixations on object-centred design.